Structural evolution and growth mechanisms of RF-magnetron sputter-deposited hydroxyapatite thin films on the basis of unified principles; Applied Surface Science; Vol. 425 - Ivanova A. A. Anna Aleksandrovna; Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich; Depla D. Diederik (2017, 2017)
Title screen